Graphite negative electrode active material based on fluidized bed method and preparation method of graphite negative electrode active material
By using the fluidized bed method to coat the MoxOyPz layer on the surface of the graphite negative electrode, the poor contact between the graphite negative electrode and the sulfide solid electrolyte and the battery cycle life are solved, and the excellent rate performance and cycle stability of the all-solid state battery are achieved.
Patent Information
- Application Number
- CN202411600960.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-14
AI Technical Summary
The poor interface contact between the graphite negative electrode and the sulfide solid electrolyte and the decomposition and deterioration of the sulfide solid electrolyte during the cycle, resulting in poor rate performance and cycle life of the all-solid state battery.
A MoxOyPz layer containing molybdenum and phosphorus was uniformly coated on the surface of the graphite negative electrode by fluidized bed method, and graphite negative electrode active material with excellent structural stability was obtained by high temperature calcination.
It effectively improves the contact between the graphite negative electrode and the sulfide solid electrolyte, inhibits the generation of high-resistance substances, and improves the rate performance and cycle stability of the battery.
Smart Images

Figure CN119627065A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a graphite negative electrode active material based on a fluidized bed method and a preparation method thereof. Background Art
[0002] The booming new energy vehicle market has led to a sharp increase in demand for high-performance lithium-ion batteries. The performance and market acceptance of new energy vehicles largely depend on the performance of lithium-ion batteries, including energy density, safety, cycle stability, cost, and charging rate. At present, all-solid-state batteries have become the target of the lithium battery industry due to their extremely high energy density and ultra-high safety. Among them, sulfide all-solid-state batteries have become a hot topic of concern due to their higher energy density, ultra-high safety, and easier implementation.
[0003] As the most widely used negative electrode material, graphite negative electrode has excellent structural stability, low cost and good rate performance. It is easier to choose it as the negative electrode material of sulfide solid-state battery in industry. However, the main difficulty of using graphite negative electrode in sulfide solid electrolyte is the continuous decomposition and degradation of sulfide solid electrolyte on the surface of graphite negative electrode and the poor contact between the two.
[0004] 1. The interface contact problem between the sulfide solid electrolyte and the graphite negative electrode: The contact between the graphite negative electrode and the sulfide solid electrolyte is solid-solid contact. If the two are not evenly dispersed, it will make it difficult for some silicon negative electrodes to directly obtain lithium ions from the sulfide solid electrolyte, resulting in poor rate performance of the battery.
[0005] 2. The problem of poor cycle life of sulfide-graphite negative electrode all-solid-state batteries: Since the sulfide solid electrolyte will continuously decompose and degrade on the surface of the graphite negative electrode during the cycle, it will produce by-products with high resistivity, which seriously hinders the Li+ transmission between the graphite negative electrode and the sulfide solid electrolyte, and increases the battery polarization. As the cycle progresses, the capacity of the graphite-sulfide all-solid-state battery will gradually decay, so the all-solid-state battery exhibits poor rate performance.
[0006] Therefore, it is necessary to provide a graphite negative electrode active material based on a fluidized bed method and a preparation method thereof, so as to improve the rate performance and cycle performance of an all-solid-state battery. Summary of the invention
[0007] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a graphite negative electrode active material based on a fluidized bed method and a preparation method thereof, so as to improve the rate performance and cycle performance of an all-solid-state battery.
[0008] A first aspect of the present invention provides a graphite negative electrode active material based on a fluidized bed method.
[0009] Specifically, graphite and Mo x O y P z layer;
[0010] The Mo x O y P z A layer is coated with the graphite;
[0011] Among them, 0.50<x<0.95, 0.15<y<1.45, and 0.35<z<0.98.
[0012] Preferably, 0.60<x<0.95, 0.20<y<1.40, 0.45<z<0.98.
[0013] Preferably, the graphite negative electrode active material has a D 50 The surface area is 8-40 μm and the specific surface area is 0.8-3.4 m 2 / g.
[0014] Further preferably, the D of the graphite negative electrode active material 50 The surface area is 8 to 20 μm and the specific surface area is 1 to 6 m 2 / g.
[0015] More preferably, the graphite negative electrode active material has a D 50 The surface area is 8 to 15 μm and the specific surface area is 2 to 5 m 2 / g.
[0016] Preferably, the graphite has a D 50 The nanostructured carbon fiber is 5 to 30 μm and the reversible capacity is 330 to 400 mAh / g.
[0017] Further preferably, the graphite D 50 The nanostructured carbon nanotubes are 5 to 20 μm in size and have a reversible capacity of 330 to 380 mAh / g.
[0018] More preferably, the graphite has a D 50 It is 5 to 10 μm and has a reversible capacity of 350 to 380 mAh / g.
[0019] Preferably, the graphite is artificial graphite.
[0020] A second aspect of the present invention provides a method for preparing a graphite negative electrode active material.
[0021] Specifically, the following steps are included:
[0022] (1) Placing graphite in a fluidized bed, filling it with protective gas, and then turning on the fluidized bed to allow the graphite to float in the fluidized bed;
[0023] (2) dissolving a molybdenum source in a solvent to obtain a molybdenum source solution, and controlling the speed of a peristaltic pump to add the molybdenum source solution into the fluidized bed and coat the graphite;
[0024] (3) controlling the temperature in the fluidized bed chamber, heating up the gasified phosphorus source and pumping it into the fluidized bed for deposition to obtain a semi-finished material;
[0025] (4) The semi-finished material is taken out and calcined at high temperature to obtain a graphite negative electrode active material.
[0026] Preferably, in step (1), the parameters for starting the fluidized bed include: the fan air volume is 100 to 200 m 3 / h, turntable speed is 100-200rpm, inlet air temperature is 50-100℃, and material temperature is 50-100℃.
[0027] Further preferably, in step (1), the parameters for starting the fluidized bed include: the fan air volume is 150 to 200 m 3 / h, turntable speed is 150-200rpm, inlet air temperature is 50-80℃, and material temperature is 50-80℃.
[0028] More preferably, in step (1), the parameters for starting the fluidized bed include: the fan air volume is 150m 3 / h, turntable speed is 150rpm, inlet air temperature is 70℃, and material temperature is 60℃.
[0029] Preferably, in step (2), the solvent includes at least one of water, ethanol, dimethyl ether, tetrahydrofuran, ethylene glycol dimethyl ether, and methyl tert-butyl ether.
[0030] Preferably, in step (2), the rotation speed of the peristaltic pump is 1 to 10 rpm.
[0031] Further preferably, in step (2), the rotation speed of the peristaltic pump is 1 to 5 rpm.
[0032] More preferably, in step (2), the rotation speed of the peristaltic pump is 4 rpm.
[0033] Preferably, in step (2), the molybdenum source includes at least one of ammonium molybdate, sodium molybdate, iron molybdate, and dodecamolybdate heteropolyacid salt.
[0034] Further preferably, the dodecamolybdate heteropolyacid salt includes at least one of sodium phosphomolybdate and ammonium phosphomolybdate.
[0035] Preferably, in step (3), the phosphorus source includes at least one of red phosphorus, white phosphorus, black phosphorus and sodium hypophosphite.
[0036] Preferably, the mass ratio of the graphite, the molybdenum source and the phosphorus source is (100-500):(2-10):3.
[0037] Further preferably, the mass ratio of the graphite, the molybdenum source and the phosphorus source is (150-450):(2-8):3.
[0038] More preferably, the mass ratio of the graphite, the molybdenum source and the phosphorus source is (200-400):(2-6):3.
[0039] Preferably, in step (3), the temperature in the chamber is 200-350° C. and maintained for 1-20 hours.
[0040] Further preferably, in step (3), the temperature in the chamber is 280-350° C. and maintained for 1-10 hours.
[0041] More preferably, in step (3), the temperature in the chamber is 290° C. and is maintained for 1 hour.
[0042] Preferably, in step (2), the molybdenum source is in the form of a solution with a solution concentration of 0.1 to 0.5 mol / L.
[0043] Preferably, in step (2), the molybdenum source is in the form of a solution with a concentration of 0.1 to 0.3 mol / L.
[0044] Further preferably, in step (2), the molybdenum source is in the form of a solution with a solution concentration of 0.1 to 0.2 mol / L.
[0045] Preferably, in step (4), the high temperature calcination is carried out at a temperature of 500 to 800° C. and for a time of 2 to 12 hours.
[0046] Further preferably, in step (4), the high temperature calcination is carried out at a temperature of 600 to 800° C. and for a time of 2 to 5 hours.
[0047] More preferably, in step (4), the high temperature calcination is carried out at a temperature of 600° C. and for a time of 2 h.
[0048] Preferably, in step (1), the protective gas includes at least one of argon and nitrogen.
[0049] A third aspect of the present invention provides a negative electrode.
[0050] Specifically, the negative electrode includes the graphite negative electrode active material provided in the first aspect.
[0051] A fourth aspect of the present invention provides an all-solid-state lithium-ion battery.
[0052] Specifically, the all-solid-state lithium-ion battery includes the negative electrode provided by the third aspect.
[0053] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0054] The graphite negative electrode active material prepared by the present invention has excellent cycle stability and rate performance. A layer of material containing molybdenum and phosphorus is uniformly coated on the surface of graphite based on a fluidized bed, and Mo with excellent structural stability is obtained by high-temperature calcination. x O y P z , which is evenly coated on the graphite surface, can effectively prevent the direct contact between the sulfide solid electrolyte and the graphite negative electrode, inhibit the generation of high-resistance materials, avoid the increase of battery polarization and the deterioration of the rate; and it can receive Li during the first lithiation process + Form a fast transmission channel to accelerate Li + Transmission; thanks to Mo x O y P z During the first round of lithiation, the lithium-rich intermediate layer will firmly bond the graphite and sulfide solid electrolyte, thereby effectively improving the contact between the two and reducing the interface resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 The figure is a test result of the rate performance of the all-solid-state lithium-ion battery composed of the graphite negative electrode active material of Example 1 and Comparative Example 3;
[0056] Figure 2 This is a graph showing the results of scanning electron microscopy testing and energy dispersive X-ray spectroscopy testing in Example 1. DETAILED DESCRIPTION
[0057] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0058] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0059] Example 1
[0060] A graphite negative electrode active material based on a fluidized bed method and a preparation method thereof.
[0061] Graphite negative electrode active material: graphite and Mo 0.79 O 0.92 P 0.65 Layer composition; Mo 0.79 O 0.92 P 0.65Layer coated graphite, where the graphite D 50 =9.70, reversible capacity 373.19 mAh / g.
[0062] The specific preparation method is as follows:
[0063] (1) Place 200g of graphite inside the fluidized bed, seal the inner chamber, and fill it with argon to replace the internal air. Turn on the fluidized bed and set the fan air volume to 150m 3 / h, the rotating disk speed is 150rpm, the inlet air temperature is 70℃, and the material temperature is 60℃, so that the graphite floats inside the fluidized bed;
[0064] (2) Dissolve 2.796 g of ammonium molybdate tetrahydrate in 100 g of deionized water (the concentration of molybdenum atoms is 0.158 mol / L), stir to dissolve, control the speed of the peristaltic pump to 4 rpm, and pump the molybdenum source solution into the fluidized bed cavity to coat the graphite;
[0065] (3) Changing the internal temperature of the fluidized bed cavity to 290° C. and the inlet air temperature to 450° C., heating 2 g of red phosphorus to 450° C. to sublimate into gas, slowly injecting the gaseous red phosphorus into the fluidized bed cavity, maintaining the deposition for 1 hour, and then gradually cooling down to obtain a semi-finished material;
[0066] (4) Finally, the semi-finished material is taken out and calcined in an argon environment at a high temperature of 600°C for 2 hours to obtain a graphite negative electrode active material.
[0067] Example 2
[0068] A graphite negative electrode active material based on a fluidized bed method and a preparation method thereof.
[0069] Graphite negative electrode active material: graphite and Mo 0.95 O 1.40 P 0.65 Layer composition; Mo 0.95 O 1.40 P 0.65 Layer coated graphite, where the graphite D 50 =9.70, reversible capacity 373.19 mAh / g.
[0070] The difference from Example 1 is that the mass of ammonium molybdate tetrahydrate in Example 2 is 3.355 g. The preparation method is the same as that in Example 1.
[0071] Example 3
[0072] A graphite negative electrode active material based on a fluidized bed method and a preparation method thereof.
[0073] Graphite negative electrode active material: graphite and Mo 0.63 O 0.45 P 0.65Layer composition; Mo 0.63 O 0.45 P 0.65 Layer coated graphite, where the graphite D 50 =9.70, reversible capacity 373.19 mAh / g.
[0074] The difference from Example 1 is that the mass of ammonium molybdate tetrahydrate in Example 3 is 2.237 g. The preparation method is the same as that in Example 1.
[0075] Example 4
[0076] A graphite negative electrode active material based on a fluidized bed method and a preparation method thereof.
[0077] Graphite negative electrode active material: graphite and Mo 0.79 O 0.20 P 0.97 Layer composition; Mo 0.79 O 0.20 P 0.97 Layer coated graphite, where the graphite D 50 =9.70, reversible capacity 373.19 mAh / g.
[0078] The difference from Example 1 is that the mass of red phosphorus in Example 4 is 3.0 g. The preparation method is the same as that in Example 1.
[0079] Example 5
[0080] A graphite negative electrode active material based on a fluidized bed method and a preparation method thereof.
[0081] Graphite negative electrode active material: graphite and Mo 0.79 O 1.29 P 0.48 Layer composition; Mo 0.79 O 1.29 P 0.48 Layer coated graphite, where the graphite D 50 =9.70, reversible capacity 373.19 mAh / g.
[0082] The difference from Example 1 is that the mass of red phosphorus in Example 5 is 1.5 g. The preparation method is the same as that in Example 1.
[0083] Comparative Example 1
[0084] A graphite negative electrode active material and a preparation method thereof.
[0085] Graphite negative electrode active material: graphite and Mo 0.79 O 2.38 P 3.23 Layer composition; Mo 0.79 O2.38 P 3.23 Layer coated graphite, where the graphite D 50 =9.70, reversible capacity 373.19 mAh / g.
[0086] The specific preparation method is as follows:
[0087] 200 g of graphite, 2.796 g of ammonium molybdate tetrahydrate, and 2.0 g of red phosphorus were ball-milled at 500 rpm for 1 h, and then the sample was calcined at 600° C. in an argon environment for 2 h to obtain a graphite negative electrode active material.
[0088] Comparative Example 2
[0089] A graphite negative electrode active material based on a fluidized bed method and a preparation method thereof.
[0090] Graphite negative electrode active material: graphite and Mo 0.79 O 2.38 P 6.46 Layer composition; Mo 0.79 O 2.38 P 6.46 Layer coated graphite, where the graphite D 50 =9.70, reversible capacity 373.19 mAh / g.
[0091] The difference from Example 1 is that the mass of red phosphorus in Comparative Example 2 is 5 g. The preparation method is the same as that of Example 1.
[0092] Comparative Example 3
[0093] A graphite negative electrode active material and a preparation method thereof.
[0094] Graphite negative electrode active material: directly composed of the graphite in Example 1, without including a coating layer.
[0095] 1. Characterization of physical and chemical properties of materials.
[0096] The graphite negative electrode active materials of Examples 1 to 5 and Comparative Examples 1 to 3 were tested by a Malvern laser particle size analyzer to obtain the median particle size D of the materials. 50 , and the Brunauer-Emmett-Teller (BET) test was performed to obtain the specific surface area of the material. The test results are shown in Table 1.
[0097] Table 1 Median particle size and specific surface area of each graphite negative electrode active material
[0098]
[0099]
[0100] 2. Microscopic morphology characterization.
[0101] Scanning electron microscope (SEM) test and energy dispersive X-ray spectroscopy (EDS) test were performed on Example 1, and the results are as follows: Figure 2 The Mo and P elements are evenly distributed on the micron-scale graphite surface, indicating that Example 1 achieves uniform Mo distribution on the graphite surface. x O y P z Coating. The surface is evenly coated with Mo x O y P z It can effectively improve the interfacial contact between graphite and sulfide solid electrolyte and form a fast lithium ion conductor during the first lithium insertion process, thereby achieving excellent rate performance.
[0102] 3. Electrochemical performance test.
[0103] The graphite negative electrode active materials of Examples 1 to 5 and Comparative Examples 1 to 3 were mixed with LiP 6 S 5 Cl, vapor-grown carbon fiber (VGCF), and polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 60:37:2:1 to form a composite negative electrode, and a negative electrode sheet of a suitable size was obtained through a roller-pressing and slicing process. The negative electrode sheet was then placed in a polyetheretherketone tube with a diameter of 10 mm, and then 100 mg of LiP 6 S 5 Cl was added into the tube, which was pressed into shape at a pressure of 30 MPa and tightly contacted with the negative electrode sheet. Finally, an indium sheet and a lithium sheet were added to the other side of the solid electrolyte and pressed into shape at a pressure of 4 tons to prepare an all-solid-state lithium-ion battery with a three-layer structure (composite negative electrode / solid electrolyte / Li-In alloy).
[0104] (1) Cycle performance test conditions: At 60°C, the first and second cycles were activated with a current of 0.1C, followed by a cycle test with a current of 0.5C, the test cut-off voltage was -0.61 to 0.9V, and the battery was tested under a pressure of 25MPa. The test method for the first cycle discharge specific capacity is: the first cycle constant current discharge is performed at 60°C with a current of 0.1C; the calculation formula for the 50-cycle specific capacity retention rate (%) is: 50-cycle specific capacity retention rate = (50th cycle discharge specific capacity / 3rd cycle discharge specific capacity) × 100%, and the results are shown in Table 2.
[0105] Table 2: Cyclic performance results of all-solid-state lithium-ion batteries composed of Examples 1 to 5 and Comparative Examples 1 to 3
[0106]
[0107]
[0108] The all-solid-state lithium-ion battery composed of Example 1 exhibited the best cycle stability, with a first cycle specific capacity of 398.18 mAh / g, and a capacity retention rate of 97.17% after 50 cycles at 0.5C. The all-solid-state lithium-ion batteries composed of Examples 2 to 5 also exhibited excellent cycle stability, with a 50-cycle specific capacity retention rate of more than 96%. On the contrary, the all-solid-state lithium-ion batteries composed of Comparative Examples 1 to 3 exhibited poor cycle stability and were difficult to meet practical application requirements.
[0109] (2) Rate performance test conditions: 0.1C current activation was performed at 60°C for the first and second cycles, followed by 5 cycles at 0.5C, 0.8C, 1C, and 2C respectively. The test cutoff potential was -0.61 to 0.9V, and the battery was tested at a pressure of 25MPa.
[0110] The rate performance tests of the all-solid-state lithium-ion batteries of Example 1 and Comparative Example 3 were performed respectively, and the results are as follows: Figure 1 Example 1 exhibits excellent rate performance, which is attributed to the Mo coated on its surface. 0.79 O 0.92 P 0.65 The layer effectively inhibits the degradation and decomposition of the sulfide solid electrolyte in the graphite negative electrode material, and the Mo after lithium insertion 0.79 O 0.92 P 0.65 The layer has high ionic conductivity and effectively stabilizes the Li + transmission, which is beneficial to Li + Fast transmission to achieve high rate performance and cycle stability.
[0111] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution obtained by any modification, equivalent replacement, improvement, etc. made by a person skilled in the art based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art shall be within the scope of protection determined by the claims.
Claims
1. A graphite negative electrode active material based on a fluidized bed method, characterized in that: Including graphite and Mo x O y P z layer; The Mo x O y P z A layer is coated with the graphite; Among them, 0.50<x<0.95, 0.15<y<1.45, and 0.35<z<0.
98.
2. The graphite negative electrode active material according to claim 1, characterized in that The graphite negative electrode active material D 50 The surface area is 8 to 40 μm and the specific surface area is 0.8 to 3.4 m 2 / g.
3. The graphite negative electrode active material according to claim 1, characterized in that The graphite D 50 The nanostructured carbon fiber is 5 to 30 μm and the reversible capacity is 330 to 400 mAh / g.
4. The method for preparing a graphite negative electrode active material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Placing graphite inside a fluidized bed, filling it with protective gas, and then turning on the fluidized bed to allow the graphite to float inside the fluidized bed; (2) dissolving a molybdenum source in a solvent to obtain a molybdenum source solution, and controlling the speed of a peristaltic pump to add the molybdenum source solution into the fluidized bed and coat the graphite; (3) controlling the temperature in the fluidized bed chamber, heating up the gasified phosphorus source and pumping it into the fluidized bed for deposition to obtain a semi-finished material; (4) The semi-finished material is taken out and calcined at high temperature to obtain a graphite negative electrode active material.
5. The preparation method according to claim 4, characterized in that: In step (2), the molybdenum source includes at least one of ammonium molybdate, sodium molybdate, iron molybdate, and dodecamolybdate heteropolyacid salt.
6. The preparation method according to claim 4, characterized in that: In step (3), the phosphorus source includes at least one of red phosphorus, white phosphorus, black phosphorus, and sodium hypophosphite.
7. The preparation method according to claim 4, characterized in that: The mass ratio of the graphite, the molybdenum source and the phosphorus source is (100-500):(2-10):
3.
8. The preparation method according to claim 4, characterized in that: In step (2), the molybdenum source is in the form of a solution, and the concentration of the solution is 0.1 to 0.5 mol / L.
9. A negative electrode, characterized in that: The negative electrode comprises the graphite negative electrode active material according to any one of claims 1 to 3.
10. An all-solid-state lithium-ion battery, characterized in that: The all-solid-state lithium-ion battery comprises the negative electrode according to claim 9.